HIV, HSV2 and Syphilis Prevalence in Female Sex Workers in Kerman, South-East Iran; Using Respondent-Driven Sampling - S Navadeh; A Mirzazadeh; L Mousavi; AA Haghdoost; N Fahimfar; A Sedaghat (Tehran University of Medical Sciences, 2012)
Background: We estimated the prevalence of HIV, sexually transmitted infections (STIs), and risky behaviors among female sex workers (FSW) in Kerman City, Iran.Methods: Women, 18 years or older, who reported selling sex for at least 6 months during their lifetime and had at least one sexual contact with a client in the recent 12 months were sampled using Responding Driven Sampling (RDS). Participants were interviewed about their sexual behaviors and provided whole blood for HIV, syphilis, and Herpes simplex type 2 (HSV2) testing. Data were analyzed using RDSAT Version 6.0 software.Results: Among samples of 177 FSW, we did not find any HIV positive cases. The weighted prevalence of syphilis and HSV2 were 7.2% and 18.0%, respectively. The reported STI syndromes for the proceeding year of the survey were 36%. Unprotected sexual contact was about 17-22% and link to injecting drug users through injection was about 18%.Conclusion: While this survey found no HIV, there were findings of risky sexual behaviors and STI, markers for potential infection for HIV. The prevalence of STI and sexual risk behaviors for HIV is considerably high in this subpopulation that alarming for an urgent public health preventive measures and national control-plan to be developed and implemented.